Socialization on Public Service Standards in Ohoi Faan, Kei Kecil District, Southeast Maluku Regency - WAISAPY, Jeanly; RAHAWARIN, Mohamad Arsad; SELANNO, Hendry (Community Services: Sustainability Development, 2025)
The public service standards outreach program in Ohoi Faan, Kei Kecil Subdistrict, Southeast Maluku Regency, aims to improve service quality for the community in line with excellent service principles. These standards include transparency, accountability, responsiveness, fairness, and effectiveness. Transparency emphasizes the importance of the village office providing clear, accessible, and open information, such as the types of services, process flow, and the rights and responsibilities of the public. It ensures the community understands the services they receive. Accountability requires service providers to take responsibility for their actions and decisions, adhere to established procedures, prevent discrimination, and maintain integrity. Responsiveness demands that staff respond promptly and appropriately to community requests and complaints, enhancing public satisfaction by meeting their needs efficiently. Fairness ensures that all residents receive equal services without discrimination based on race, religion, gender, or social status, fostering social justice. Effectiveness and efficiency focus on optimizing resources to deliver quality services while saving time and costs for both service providers and recipients. The outreach program also encourages active community participation in evaluating services by providing constructive feedback and suggestions. Service providers are expected to respond positively to feedback to achieve continuous improvement. By understanding public service standards, village officials can deliver services more professionally and responsibly, while the community feels valued and gains greater trust in the local government. This outreach initiative strengthens the relationship between the government and the community, creating a better service environment.